AIMS workshop for effective academic course planning and delivery 2023 / Syahida Fathiah Ahmad Kamal and Dr. Gurmeet Kaur Surindar Singh - Ahmad Kamal, Syahida Fathiah; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
The Academic Office has organised a course file refinement workshop on April 5th, 2023, at The Gallery, Level 5, FF1 Building, Faculty of Pharmacy, Puncak Alam Campus, Universiti Teknologi MARA (UiTM). The workshop was chaired by Dr. Mohd Shahezwan Abd Wahab, Deputy Dean of Academic Affairs, Faculty of Pharmacy, and was attended by 35 lecturers, all of whom were resource persons (RPs) for the courses offered at the Faculty of Pharmacy. The purpose of the workshop was to provide training and guidance to the RPs on how to update and refine course files in the Academic Information Management System (AIMS), which is the university's online database for managing data on courses offered by the faculty.